Perancangan Sistem Informasi Koperasi Simpan Pinjam Berbasis Web Menggunakan Metode Extreme Programming (Studi Kasus : PT. Megariamas Sentosa) - Ilham Pratama; Sartika Lina Mulani Sitio (CV. Multi Kreasi Media, 2024)
Savings and Loans Cooperative at Pt. Megariamas Sentosa is currently still experiencing some deficiencies in implementing this savings and loan cooperative system. In view of the process of applying for savings and loans, the submission process is carried out by coming to the cooperative management section at the PT. MEGARIAMAS SENTOSA with several requirements for submitting deposits and loans. Then a personal data entry form and savings and loan options are provided. and if there is a loan, the cooperative members submit loan application data to the cooperative operator. then the operator will issue a loan fee as well as the amount of the tenor and installments determined by the cooperative with the nominal amount of the loan proposed. Cooperatives still have several deficiencies in the internal control process, namely member data processing is still carried out using written media on the application form. and archiving is carried out so that the data search process must be carried out one by one or in pieces to find member data as well as information on savings and loans that have been carried out. Seeing this, we need an information system that can handle business processes in savings and loan cooperatives, especially in managing members and saving and loan transactions. This study aims to build a savings and loan cooperative information system through the application of the Extreme Programming (XP) method. This method can be run with small to medium scale teams.